Robust Genetic Circuit Design: A Mixed H∞ and IQC Analysis - Ruijuan Chen; Wei Pan; Dongfei Fu; Xin He (Advances in Mathematical Physics)
This paper considers the problem of designing a genetic circuit which is robust to noise effect. To achieve this goal, a mixed H∞ and Integral Quadratic Constraints (IQC) approach is proposed. In order to minimize the effects of external noise on the genetic regulatory network in terms of H∞ norm, a design procedure of Hill coefficients in the promoters is presented. The IQC approach is introduced to analyze and guarantee the stability of the designed circuit.